Gender Wage Gaps and Risky vs. Secure Employment: An Experimental Analysis - Seeun Jung; Chung Choe; Ronald L. Oaxaca (Institute for the Study of Labor (IZA), 2016)
In addition to discrimination, market power, and human capital, gender differences in risk preferences might also contribute to observed gender wage gaps. We conduct laboratory experiments in which subjects choose between a risky (in terms of exposure to unemployment) and a secure job after being assigned in early rounds to both types of jobs. Both jobs involve the same typing task. The risky job adds the element of a known probability that the typing opportunity will not be available in any given period. Subjects were informed of the exogenous risk premium being offered for the risky job. Women were more likely than men to select the secure job, and these job choices accounted for between 40% and 77% of the gender wage gap in the experiments. That women were more risk averse than men was also manifest in the Pratt-Arrow Constant Absolute Risk Aversion parameters estimated from a random utility model adaptation of the mean-variance portfolio model.
Keywords: J16; J24; J31; C91; D81; 330; occupational choice; gender wage differentials; risk aversion; lab experiment